Design Strategy for Designing a Service in Malaysia - Majid, Ahmad Zuhairi Abdul (Science & Engineering Research Support Society, 2019)
In the rapid development of new technologies, Malaysian has never left behind to experience new products and services. With new design thinking, principles and methods for service development will change the values of designers in education and creative industries suitable for the next generation. The understanding “dream society” of the next generation that will merge with the understanding of experience economy can build the service environment more sustainable. The new generation of mankind is looking for personal satisfaction with emotional value to their lives. A set of questionnaires was constructed through an analysis of keywords from literature reviews employing KJ method. In order to fulfill the objective, quantitative data were analyzed to see how customer perceive the automobile service centers while knowing their character and preferences. This research will give an allocation for industrial designers to play their role in helping the industry efficiently on quality concept of service design development in Malaysia. Result presented herein based on a survey and the scenario of Malaysian automotive service centers.